A "one stop" thermal stabilizer, zinc arginine complex, with excellent comprehensive thermal stability effect on poly(vinyl chloride). (September 2019) - Shi, Yanqin; Lu, Songyan; Ma, Biao; Ma, Meng; He, Huiwen; Chen, Si; Wang, Xu
Abstract: A "one stop" thermal stabilizer, zinc arginine complex (Zn(Arg)2 ), with excellent excellent initial whiteness, whiteness retention and long-term thermal stability time for PVC, was conveniently synthesized in water solution. The successful synthesis of Zn(Arg)2 was confirmed by FTIR, TGA and element analysis. Besides the longer Congo red and static thermal stability time than nitrogen-containing thermal stabilizer reported, Zn(Arg)2 also had better initial whiteness, whiteness retention and dynamic thermal stability time showed by Congo red test, discoloration test and torque rheology test. Especially, the static thermal stability time was more than 150 min, and the dynamic thermal stability time reached 78 min. The excellent thermal stability effect of Zn(Arg)2 on PVC was ascribed to the simultaneous possession of three mechanisms: absorbing HCl, replacing labile chlorine atoms and complexing ZnCl2 . Moreover, PVC with Zn(Arg)2 also showed excellent transmittance tested by vis-uv-near infrared spectrophotometer. Therefore, Zn(Arg)2 is a "one stop" thermal stabilizer with good application prospects in transparent PVC. Highlights: Zinc arginine complex was synthesized in water solution. Zinc arginine complex has excellent initial whiteness, whiteness retention and long-term thermal stability at once for PVC. Zinc arginine complex could absorb HCl, replace unstable chlorine atoms, complex ZnCl2 and reduce "zinc burning" effect. PVC sheet with zinc arginine complex exhibits super high transmittance.